2011
DOI: 10.1590/s0102-695x2011005000062
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of algae in photobioreator and obtention of biodiesel

Abstract: In this work we described the cultivation of Chlorella vulgaris in a photobioreactor to algal biomass production. The dried biomass was used as feedstock for biodiesel production, it presented 26% lipids and via sonocatalysis stage of the methodology resulted in 60% of fatty acid methyl esters (FAME). The FAME content was confirmed by Gas Chromatography (GC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
4
0
5
Order By: Relevance
“…U svrhu daljeg unapređenja in situ proizvodnje biodizela iz algi ispitivana je primena ultrazvuka [123,124], mikotalasnog zračenja [120,124], kao i primena kosolvenata [125]. Takođe, sprovedena je optimizacija procesnih faktora primenom metodologije površine odziva [112,113,120,[126][127][128].…”
Section: Unapređenje Procesa In Situ Transesterifikacijeunclassified
See 1 more Smart Citation
“…U svrhu daljeg unapređenja in situ proizvodnje biodizela iz algi ispitivana je primena ultrazvuka [123,124], mikotalasnog zračenja [120,124], kao i primena kosolvenata [125]. Takođe, sprovedena je optimizacija procesnih faktora primenom metodologije površine odziva [112,113,120,[126][127][128].…”
Section: Unapređenje Procesa In Situ Transesterifikacijeunclassified
“…Ultrazvuk ima sve veću ulogu u hemijskim procesima, naročito u slučajevima kada klasične metode zahtevaju drastične uslove ili veoma dugo trajanje reakcije i predstavlja važno sredstvo zelene hemije u smislu minimizacije otpada i uštede energije [123]. Mikrotalasno zračenje se, takođe, koristi poslednjih godina kao efikasan način skraćivanja vremena reakcije trans-esterifikacije.…”
Section: Primena Ultrazvuka I Mikrotalasnog Zračenjaunclassified
“…O percentual de ésteres obtido foi de 60%. 33 Além dos estudos para melhorar os rendimentos das reações de transesterificação, recentemente muitos avanços foram efetuados na área de cultivo e bioprospecção de microalgas, visando a obtenção de biodiesel. Neste sentido, Doan e colaboradores coletaram 21 espécies de microalgas das águas costeiras da Singapura e avaliaram vários parâmetros, como, taxa de crescimento celular, concentração de biomassa, conteúdo lipídico e perfil de ácidos graxos.…”
Section: Processos De Transesterificaçãounclassified
“…Thus, the remediation of wastewater by using microalgae is an environmentally friendly process that does not generate secondary pollutants and yields biomass that can be reused, enabling efficient recycling of nutrients (Munoz & Guieyesse, 2006). Besides their use in bioremediation and biofuel production, microalgae can also be used as additives in animal feed and for the extraction of added-value products such as carotenoids and other biomolecules (Rawat et al, 2011;Hobuss et al, 2011;Soares et al, 2012).…”
Section: Microalgaementioning
confidence: 99%
“…The separation of algal biomass can be accomplished by methods such as centrifugation, flocculation, sedimentation, microfiltration and combinations of these (Grima et al, 2003;Munoz & Guieyesse, 2006;Danquah et al, 2009;Mutanda et al, 2011). Hobuss et al (2011) reported a preliminary study of biodiesel production by the microalgae Chlorella vulgaris Beijerinck cultivated in a photobioreactor; the biodiesel was obtained in a significantly shorter time and with good lipid productivity.…”
Section: Microalgaementioning
confidence: 99%